Pemanfaatan Layanan American Corner di UPT Perpustakaan Universitas Andalas - Aprilla, Suci Anom; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discussed about Utilization Service American Corner at Andalas University Library. The utilization of services at the American Corner Library Andalas University. The method used in this research is descriptive method. Data were collected through observation and interviews as well as the spaciousness of literary study using books and reading are considered related to the discuss in the paper. Based on the results of the discussion in the American Corner at Andalas University Library Unit, it can be concluded that there are services and utilization at the American. The American Corner services include: 1) Service Voluntter; 2) Collection Services; 3) Service Activities and Events; 4) Multimedia Services, and the utilization of American Corner, namely: 1) to take advantage of the Internet network; 2) to learn English; 3) to take advantage of the collection comes straight from America.Â Keyword: American Corner, American cornerâ€™s Service